Multiphysics modeling using COMSOL5 and MATLAB - Pryor, Roger (Dulles, Virginia : Mercury Learning and Information, 2016)
"COMSOL 5 and MATLAB are valuable software modeling tools for engineers and scientists. This book explores a wide range of models in coordinate systems from 0D to 3D and introduces the numerical analysis techniques employed in COMSOL 5 (including Application Builder) and MATLAB software. The text presents electromagnetic, electronic, optical, thermal physics, and biomedical models as examples. It presents the fundamental concepts in the models and the step-by-step instructions needed to build each model. The book is designed to introduce modeling to an experienced engineer or can also be used for upper level undergraduate or graduate courses." --
1. Modeling Methodology. 2. Materials Properties. 3. 0D Electrical Circuit Interface. 4. 1D. 5. 2D. 6. 2D Axisymmetric. 7. 2D Simple Mixed Mode. 8. 2D Complex Mixed Mode. 9. 3D. 10. Perfectly Matched Layer Models. 11. Bioheat Models. Appendices. About the DVD.
Includes bibliographical references and index.
Keywords: COMSOL Multiphysics; MATLAB; Engineering -- Data processing; Engineering -- Mathematical models; Engineering -- Computer simulation; Physics -- Data processing; Physics -- Mathematical models; Physics -- Computer simulation